Estudo da ingestão e retenção gástrica de solução hipertônica de nacl em ratos com hipertensão renovascular 2-rins-1-clipe - Lima, Rian Victor Silva (2023)
Arterial hypertension (AH) is a chronic disease that causes structural/functional changes in heart, blood vessels, kidneys and brain. Its pathophysiology can be studied using the 2-kidneys-1-clip (2K1C) experimental model, characterized by an increase in circulating renin with activation of the renin-angiotensin system (RAS). In addition to the hemodynamic and autonomic responses of this model, it was recently demonstrated, in the first 6 weeks post-induction, a transient increase in spontaneous intake of 0.3 M NaCl and water in 2K1C rats concomitant with persistent hyperreninemia. Another study demonstrated gastrointestinal (GI) dysmotility in 2K1C rats, characterized by reduced gastric emptying (GE) of glucose-containing (isotonic) solution. Considering that gastrointestinal afferent pathways activate the hydromineral ingestion inhibitory system and that both the central areas involved in GI autonomic control and the gastric tissue itself can be modulated by RAS, the changes in the hydromineral ingestion pattern observed in 2K1C rats may be related to GI Dysmotility. Therefore, in this study we investigated whether 2K1C animals present changes in GE in hypertonic NaCl solutions. Wistar rats (180 to 220 g) were submitted to the 2K1C surgical protocol or normotensive group (Sham). After a period of surgical recovery, the animals were transferred to metabolic cages with food, water and NaCl (0.23 M or 0.3 M) available. Daily food and liquid intake was measured between the 22nd and 28th post-surgical day (DPC). On the 29th DPC, gastric retention (RG) was assessed 7.5 or 15 minutes after administration of the test solution by gavage (1.5 ml or 3 ml) of NaCl (0.15 M, 0.23 M or 0. 3 M). On the 28th DPC, 2K1C rats had higher intakes of 0.23 M (36 ± 11 ml, n = 5) and 0.3 M (13 ± 2 ml, n = 61) of NaCl compared to Sham (12 ± 5 ml, n = 6). and 8 ± 1 ml, n = 41, respectively, p < 0.05); no difference was observed between the groups regarding water intake. There was no difference between groups in GR of 1.5 ml of 0.15 M and 0.3 M NaCl at 7.5 min (2K1C 0.15 M: 33.9 ± 2.1%, n = 8; 2K1C 0.3 M: 35.5 ± 2.4%, n = 11 vs. Sham 0.15 M: 34.3 ± 3.0%, n = 7; Sham 0.3 M: 38.6 ± 2, 0%, n = 7). There was no difference in the GR of 1.5 ml of 0.3 M NaCl at 15 min between 2K1C (24.8 ± 0.5%, n = 10) and Sham (30.6 ± 2.1%, n = 9). There was also no difference in the GR of 3 ml of 0.3 M NaCl at 15 min between 2K1C (32.5 ± 2.1%, n = 9) and Sham (28.1 ± 2.3%, n = 6). Regarding the GR of 0.23 M, there was no difference between the 2K1C (29.5 ± 1.9%, n = 5) and Sham (27.2 ± 1.5%, n = 6) groups. Therefore, it is concluded that the increased intake of hypertonic NaCl solution in 2K1C rats is independent of changes in GE rate.